Effect of roselle (hibiscus sabdariffa) on sensing properties of chitosan film sensors on fertilizer concentration detection - Roshida Mustaffa (School of Materials Engineering, 2016)
This study was divided into three sections. Each chapter was systematically organized to contain many subjects that involved in this study and have been discussed elaborately. The first chapter contains the research background, introduction, objectives, problem statement, and scope of study. This chapter discusses briefly about the sensor, chitosan and electrodeposition technique. The second chapter describes the literature review which focusing on chitosan, roselle, electrical properties, and type of fertilizer, grape vines, sensor, thin film technology and electrochemical deposition method.